Autonomy in socially assistive robotics: a systematic review - Maure, Romain; Bruno, Barbara (Frontiers in Robotics and AI, 2025)
Socially assistive robots are increasingly being researched and deployed in various domains such as education, healthcare, service, and even as collaborators in a variety of other workplaces. Similarly, SARs are also expected to interact in a socially acceptable manner with a wide audience, ranging from preschool children to the elderly. This diversity of application domains and target populations raises technical and social challenges that are yet to be overcome. While earlier works relied on the Wizard-of-Oz (WoZ) paradigm to give an illusion of interactivity and intelligence, a transition toward more autonomous robots can be observed. In this article, we present a systematic review, following the PRISMA method, of the last 5 years of Socially Assistive Robotics research, centered around SARs’ level of autonomy with a stronger focus on fully and semi-autonomous robots than non-autonomous ones. Specifically, to analyse SARs’ level of autonomy, the review identifies which sensing and actuation capabilities of SARs are typically automated and which ones are not, and how these capabilities are automated, with the aim of identifying potential gaps to be explored in future research. The review further explores whether SARs’ level of autonomy and capabilities are transparently communicated to the diverse target audiences above described and discusses the potential benefits and drawbacks of such transparency. Finally, with the aim of providing a more holistic view of SARs’ characteristics and application domains, the review also reports the embodiment and commonly envisioned role of SARs, as well as their interventions’ size, length and environment.